Micellar and sub-micellar liquid chromatography of terephthalic acid contaminants using a C18 column coated with Tween 20 - Ali, Abd al-karim F.; Danielson, Neil D. (Analytica chimica acta, 2020)
The tremendous amounts of terephthalic acid (TPA) produced globally require consistent monitoring of its contaminants during the different stages of production for quality control purposes. In this paper, a simple, robust and green liquid chromatography method has been developed using an isocratic 100% aqueous mobile phase at pH 2 (dilute sulfuric acid) to separate TPA contaminants (mono-, di-, and tri-carboxylic aromatic acids) on a C18 stationary phase coated with Tween 20 (polyoxyethylene(20)sorbitan monolaurate). After optimization of all chromatographic conditions, near baseline separation of the nine carboxylic acids under investigation was achieved with a 2.5 mL/min flow rate on a 5 micron C18 silica column (100 x 4.6 mm) in under 20 min. The modified stationary phase showed an excellent capability to separate structural isomers in a reasonable time, markedly better that the bare C18 stationary phase. Plots of ln retention factor versus 1/temperature showed the expected linear relationship for the di- and tri-carboxylic aromatic acids (single retention mechanism likely) but a quadratic fit for the mono-carboxylic aromatic acids (dual retention mechanism likely). Due to the stability of the surfactant modified stationary phase, future potential mass spectrometry compatibility was shown through the alternative use of trifluoroacetic acid in the 100% H2O (no Tween) mobile phase but still with UV detection. The developed method with 0.001% (vol/vol) Tween in the mobile phase was successfully used to analyze two different types of TPA industrial samples for all nine components plus revealing some other impurity peaks. The lowest limit of detection was 0.010 nmoles for o-phthalic acid and p-toluic acid (PTA), while the highest was 0.065 nmoles for 4-carboxybenzaldehyde (CBA). The concentrations of these important contaminants, PTA and CBA, in the mother liquor sample were 3348 mg/L and 1806 mg/L, respectively, while their respective concentrations in the purified TPA powder were 135 mg/kg and 17.7 mg/kg. [Display omitted] •Positional aromatic isomers in industrial terephthalic acid samples separated.•“Green” chromatography using Tween 20 surfactant coated column.•Potential for mass spectrometry detection shown.